Features of the representation of the conceptual dyad Zhashau — Elyum in the Karachay-Balkarian ethnic culture - Bashieva, Svetlana K.; Ulbasheva, Zulfiya M. (The New Research of Tuva, 2025)
The article examines the features of the concepts Zhashau — Elyum (‘life — death’) in Karachay-Balkar culture, which are understood as a conceptual dyad. The cultural concepts are analyzed within the framework of Ch. K. Lamazhaa’s theory in three aspects: concept-word-forms, concept-ideas, and concept-social regulators.An analysis of the ideological content of the concepts revealed their complex structure, consisting of compound lexemes: jan ‘soul’, qadar ‘fate’, and zaman ‘time’, whose semantic content is determined by the historical and cultural experience of the Karachay-Balkar ethnic group.The etymological analysis of the concept-word-forms showed that the lexemes Zhashau and Elyum trace back to ancient Turkic roots, as evidenced by the presence of full equivalents or phonetic variants in other Turkic languages.An analysis of the ideological content of the concepts revealed their complex structure, consisting of compound lexemes: jan ‘soul’, qadar ‘fate’, and zaman ‘time’, whose semantic content is determined by the historical and cultural experience of the Karachay-Balkar ethnic group. It includes a complex of axiological characteristics: prosperous, bright, trouble-free, honest, difficult, inglorious, disgraceful, short life predetermined from above, and inevitable death. One can also speak of cognitive features in which the profound aspects of life and death are explicated (temporality in this world, immortality of the soul, belief in fate, inevitability of life scenario, transience, irreversibility of time, etc.). In the consciousness of the Karachays and Balkars, Zhashau — Elyum are understood as logically interconnected beginning and end, predetermined by fate and time.To understand the socio-regulatory aspect of the concepts, examples from the social practices of the Karachays and Balkars are provided. These examples document various ritual actions reflecting the ethnos’ attitude toward life and death, in particular, preparation for death as an inevitable fact, respect for the memory of the deceased, and memorial feasts.
Keywords: ethnic culture; Karachay-Balkar culture; cultural concept; cognitive feature; life; death; conceptual dyad